LDPE microplastic films alter microbial community composition and enzymatic activities in soil. (November 2019) - Huang, Yi; Zhao, Yanran; Wang, Jie; Zhang, Mengjun; Jia, Weiqian; Qin, Xiao
Abstract: Concerns regarding microplastic contamination have spread from aquatic environments to terrestrial systems with a growing number of studies have been reported. Notwithstanding, the potential effects on soil ecosystems remain largely unexplored. In this study, the effects of polyethylene microplastics on soil enzymatic activities and the bacterial community were evaluated, and the microbiota colonizing on microplastics were also investigated. Microplastic amendment (2000 fragments per kg soil) significantly increased the urease and catalase activities in soil after 15 days, and no discernible alteration of invertase activities was detected. Results from high-throughput sequencing of 16S rRNA revealed that the alpha diversities (richness, evenness, and diversity) of the microbiota in soil were not obviously changed by the PE amendment, whereas the diversity indexes of microbiota on plastic fragments were significantly lower than those in the control and amended soils. Different taxonomic composition was observed in between the control and amended soils after 90 days of incubation. Bacterial assemblages with distinct community structure colonized the PE microplastics. Additionally, several taxa including plastic-degrading bacteria and pathogens were more abundant on microplastics. Simultaneously, the predicted functional profiles showed that the pathways of amino acid metabolism and xenobiotics biodegradation and metabolism were higher on the microplastics. These results indicated that microplastics in soil, compared with those in aquatic environments, can also act as a distinct microbial habitat, potentially altering the ecological functions of soil ecosystems. Highlights: PE micro-films significantly increased the urease and catalase activities in soils. Alpha diversity of the microbiota was lower on PE micro-films than in soils. Community structure and metabolic pathways were different on PE micro-films. Potential plastic-degrading and pathogenic bacteria were enriched on PE fragments. The alteration of bacterial assemblages may affect terrestrial ecosystems. Abstract : PE microplastic films altered the enzymatic activities and taxonomic compositions in soils, and were colonized by bacterial assemblages with distinct community structure.